Identification and pesticide degradation test of bacterial consortium of contaminated soil - Rosariastuti, Retno; Rahmawati, Yulia; Sumani, Sumani; Hartati, Sri (Universitas Sebelas Maret, 2023)
Excessive use of pesticides in the process of cultivating shallots results in contamination of the soil. Indigenous bacteria in soil that contaminated with the chlorpyrifos pesticide suspected could used as bioremediation agent of soil contaminated with chlorpyrifos pesticide. The purpose of this study was to identify and obtain a consortium of bacteria capable in degrading pesticides on shallot fields contaminated with the pesticide chlorpyrifos. The method used in this research is the bacteria isolation using soil extract, morphological identification, molecullar identification using Next Generation Sequencing (NGS), analysis of bacterial diversity index and consortium bacterial degradation test in order to reduce levels of the chlorpyrifos pesticide. The results of this study found 16 isolates of bacteria at each study site that were resistant to 100ppm of the pesticide chlorpyrifos so that these isolates were chosen to be used as a consortium of bacteria. Molecular identification of the bacterial consortium showed that there were 10 genera consisting of Cutibacterium, Streptomyces, Staphylococcus, Ensifer, Ochrobactrum, Achromobacter, Escherichia shigella, Klebsiella, Acinetobacter, and Pseudomonas. The bacterial diversity index in shallot soils reached 2,040 and 1,467 on forest soils The reduction efficiency of the bacterial consortium using the method of growing cells and supernatant were 94.48% and 98.88%, respectively.